Pengaruh Litersi Keuangan Dan Perilaku Keuangan Terhadap Pendapatan Koperasi Kredit Swastisari di Kota Kupang - Keban, Vinsensia V.L; Kellen, Pius Bumi; Tungga, Cicilia A. (UMSurabaya Publishing, 2023)
This examine ambitions to determine the impact of economic tradition and monetary conduct on the income of Kopdit Swastisari cooperative in Kupang town. This have a look at makes use of quantitative strategies, in particular information evaluation, to process respondent survey information. To decide the pattern with the aid of easy random sampling and the pattern used on this study, 50 contributors of Swastisari cooperative in Kupang town had been the primary records. statistics have been collected the use of questionnaires disbursed to participants of the cooperative. The facts analysis techniques used on this study are more than one linear regression analysis, T-take a look at and F-test. The results of this look at display that financial culture and financial conduct have a substantial have an impact on on the earnings of Kopdit Swastisari cooperative in Kupang city. The hints on this take a look at are intended to assist individuals of the Kopdit Swastisari Cooperative in Kupang metropolis to higher apprehend price range and behavior further studies to allow extra signs and variables. Penelitian ini bertujuan buat mengetahui efek budaya keuangan serta perilaku keuangan terhadap pendapatan koperasi Kopdit Swastisari di kota Kupang. Penelitian ini menggunakan metode kuantitatif, termasuk analisis data, buat mengolah data survei responden. Penentuan sampel dilakukan dengan menggunakan metode simple secara acak sampling dan sampel yg digunakan dalam penelitian ini berjumlah 50 orang anggota Koperasi Swastisari Kota Kupang yg sebagai data utama uji dan uji F. yang akan terjadi penelitian menunjukkan bahwa Pengetahuan keuangan dan perilaku keuangan berpengaruh signifikan terhadap pendapatan. Rekomendasi penelitian ini dimaksudkan untuk membantu anggota Koperasi Kopdit Swastisari Kota Kupang lebih memahami keuangan dan melakukan penelitian lebih lanjut untuk mengaktifkan indikator dan variabel tambahan. Keywords: Literasi Keuangan, Perilaku Keuangan, Pendapatan